Can higher guy’s scores predict increased complications? exploring the link with clavien-dindo classification - Gul, Laraib; Ullah, Shuah; Bin Yousuf, Shariq; Hassan, Bazgha; Gazder, Tanzeel-Ur-Rahman; Mohsin, Rehan (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the role of guy’s stone score in predicting the complications rate for percutaneous nephrolithotomy. Method: The descriptive study was conducted at the Sindh Institute of Urology and Transplantation, Karachi, from August 2020 to February 2021, and comprised patients undergoing percutaneous nephrolithotomy. Data was collected regarding demographic, preoperative, intraoperative and postoperative variables, including Guy’s stone score and complications classified by the Clavien-Dindo system. Data was analysed with SPSS 20. Results: Of the 118 patients, 78(66%) were males, 40(34%) were females, 71(60%) were aged >30 years and 47(40%) were aged <30 years. There was a significant correlation between a higher Guy’s stone score grade and increased postoperative mild complications (p<0.0001) Conclusion: A higher Guy’s stone score did not predict severe postoperative complications among percutaneous nephrolithotomy patients. Key Words: Postoperative complications, Percutaneous nephrolithotomy, Clavien Dindo, Guys stone score, Scoring system, Stones.